Type I Interferon Response Is Mediated by NLRX1-cGAS-STING Signaling in Brain Injury - Fritsch, Lauren E.; Ju, Jing; Gudenschwager Basso, Erwin Kristobal; Soliman, Eman; Paul, Swagatika; Chen, Jiang; Kaloss, Alexandra M.; Kowalski, Elizabeth A.; Tuhy, Taylor C.; Somaiya, Rachana Deven; Wang, Xia; Allen, Irving Coy; et al. (Frontiers in Molecular Neuroscience, 2022)
Background Inflammation is a significant contributor to neuronal death and dysfunction following traumatic brain injury (TBI). Recent evidence suggests that interferons may be a key regulator of this response. Our studies evaluated the role of the Cyclic GMP-AMP Synthase-Stimulator of Interferon Genes (cGAS-STING) signaling pathway in a murine model of TBI. Methods Male, 8-week old wildtype, STING knockout (−/−), cGAS−/−, and NLRX1−/− mice were subjected to controlled cortical impact (CCI) or sham injury. Histopathological evaluation of tissue damage was assessed using non-biased stereology, which was complemented by analysis at the mRNA and protein level using qPCR and western blot analysis, respectively. Results We found that STING and Type I interferon-stimulated genes were upregulated after CCI injury in a bi-phasic manner and that loss of cGAS or STING conferred neuroprotection concomitant with a blunted inflammatory response at 24 h post-injury. cGAS−/− animals showed reduced motor deficits 4 days after injury (dpi), and amelioration of tissue damage was seen in both groups of mice up to 14 dpi. Given that cGAS requires a cytosolic damage- or pathogen-associated molecular pattern (DAMP/PAMP) to prompt downstream STING signaling, we further demonstrate that mitochondrial DNA is present in the cytosol after TBI as one possible trigger for this pathway. Recent reports suggest that the immune modulator NLR containing X1 (NLRX1) may sequester STING during viral infection. Our findings show that NLRX1 may be an additional regulator that functions upstream to regulate the cGAS-STING pathway in the brain. Conclusions These findings suggest that the canonical cGAS-STING-mediated Type I interferon signaling axis is a critical component of neural tissue damage following TBI and that mtDNA may be a possible trigger in this response.